PENGUATAN KESADARAN POLITIK GENERASI MUDA DI DESA SUKAJADI MELALUI FORUM EDUKASI PUBLIK - Asep Somanteri; Alit Wiliandani; Sania Shelvia Putri (HARUPAT: Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
Strengthening the political awareness of youth in Sukajadi Village, Cibinong District, Cianjur Regency, through a Public Education Forum represents a strategic effort to reinforce participatory democracy at the village level. The activity was conducted on December 6, 2025, at the Sukajadi Village Hall and involved local youth as primary participants. This community service program was designed using a participatory approach, engaging academics, village government officials, community leaders, and youth organizations to create an open and educational dialogue space. The program activities included seminars, group discussions, decision-making simulations, and the utilization of social media as a medium for continued communication. The results indicate a significant improvement in participants’ understanding of political concepts, village governance mechanisms, and their motivation to actively participate in local democratic processes. The public education forum successfully fostered social solidarity and collective awareness, encouraging sustained youth engagement. Furthermore, cross-stakeholder collaboration enhanced the program’s relevance and sustainability, while also creating opportunities to integrate its outcomes into village-level policymaking. This program not only equipped young people with political knowledge and skills but also strengthened an inclusive and equitable democratic culture in Sukajadi Village. The success of this initiative provides a replicable model for developing youth political capacity in other rural areas, thereby supporting the advancement of stronger grassroots democracy.